Creating and Delivering Adaptive Courses with AHA - De Bra, Paul; Smits, David; Stash, Natalia (Innovative Approaches for Learning and Knowledge Sharing, 2006)
AHA! is an Open Source adaptive hypermedia platform, resulting from 10 years of experience with creating, using and improving on-line adaptive courses and presentations. This paper focuses on some recent additions to AHA! that are especially important for adaptive educational applications, namely stable presentations, adaptive link (icon) annotations and adaptive link destinations. We not only describe the technical aspects of these parts of AHA! but also illustrate their use in educational applications. We describe some fundamental limitations of Web-based adaptive applications, and show how AHA! deals with them in order to provide adaptation to prerequisite relationships in the way one would expect.